2020
DOI: 10.1111/1759-7714.13388
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in patients with and without rheumatoid arthritis: A propensity score‐matched survival analysis cohort study

Abstract: Background Connective tissue disease increases the risk of lung cancer, but whether rheumatoid arthritis (RA) has an effect on the overall survival (OS) rate in this population has not been well studied. Methods Patients diagnosed with lung cancer between January 2015 and December 2017 were enrolled in this retrospective analysis. Propensity score matching was performed to balance the baseline of the two groups, whereas the differences between patients with and without RA were compared using survival analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…While direct comparisons cannot be made, these findings suggest the possibility that patients with RA may be experiencing earlier mortality due to complications associated with lung cancer. Zhang et al 12 . investigated the prognosis of lung cancer in a patient population in which more than 70% of patients had advanced stage III or higher lung cancer and showed that there was no significant difference in overall survival rate depending on the presence or absence of RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While direct comparisons cannot be made, these findings suggest the possibility that patients with RA may be experiencing earlier mortality due to complications associated with lung cancer. Zhang et al 12 . investigated the prognosis of lung cancer in a patient population in which more than 70% of patients had advanced stage III or higher lung cancer and showed that there was no significant difference in overall survival rate depending on the presence or absence of RA.…”
Section: Discussionmentioning
confidence: 99%
“…cancer. Zhang et al 12 investigated the prognosis of lung cancer in a patient population in which more than 70% of patients had advanced stage III or higher lung cancer and showed that there was no significant difference in overall survival rate depending on the presence or absence of RA. In our current study, although more than 60% of the patients had early-stage lung cancer, the overall survival rate of lung cancer did not differ between patients with and without RA.…”
Section: (A) (B)mentioning
confidence: 99%
“…Several studies have addressed the prognosis of patients with LC and preexisting CTDs (Table S1). Most previous studies focused on comparing cancer survival rates between patients with and without CTDs (8,(25)(26)(27)(28)(29). In 2008, Adzić et al reported on the clinical features of 24 patients with LC and CTDs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Additionally, RA patients with lung cancer, particularly those with ILD, showed lower survival rates than patients with lung cancer without RA. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Additionally, RA Horie et al • Medicine (2022) Medicine patients with lung cancer, particularly those with ILD, showed lower survival rates than patients with lung cancer without RA. [4] Organizing pneumonia (OP) is a disease response from the pulmonary reaction to harmful factors, including infections and exposure to toxic substances, drugs, and radiotherapy. [5] Furthermore, OP can be observed in autoimmune disorders including RA.…”
Section: Introductionmentioning
confidence: 99%